WHEN GOVERNANCE MATTERS: HOW GOOD CORPORATE GOVERNANCE CONDITIONS FINANCIAL DISTRESS IN INDONESIAN BANKS - Indrawati, Novita; Darlis, Edfan; Yasni, Hariadi (Universitas Riau, 2026)
This study examines the effects of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), and Corporate Social Responsibility (CSR) on financial distress in Indonesian banks during 2021–2024, with Good Corporate Governance (GCG) as a moderating variable. Financial distress is measured using the Grover model, and the hypotheses are tested through regression and Moderated Regression Analysis (MRA). The results show that CAR significantly reduces the probability of financial distress, while NPL has no significant effect. CSR is found to increase financial distress in the short term, indicating that sustainability initiatives may generate immediate financial pressure. GCG does not moderate the CAR–distress relationship, but it weakens the effect of NPL and strengthens the effect of CSR on financial distress. This study contributes by highlighting governance as a conditional mechanism rather than a universal buffer against financial risk. It demonstrates that governance interacts differently with capital structure, credit risk, and strategic CSR decisions in post-pandemic banking conditions. Practically, banks should align capital management and CSR strategies within strong governance frameworks to mitigate financial vulnerability.